1990
DOI: 10.1083/jcb.111.5.2089
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the unique NCAM VASE exon is independently regulated in distinct tissues during development.

Abstract: Abstract. During development of the rat central nervous system, neural cell adhesion molecule (NCAM) mRNAs containing in the extracellular domain a 30-bp alternative exon, here named VASE, replace RNAs that lack this exon. The presence of this alternative exon between previously described exons 7 and 8 changes the predicted loop structure of the derived polypeptide from one resembling an immunoglobulin constant region domain to one resembling an immunoglobulin variable domain. This change could have significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 42 publications
(43 reference statements)
3
64
0
1
Order By: Relevance
“…Expression of the VASE exon, encoding 10 amino acids situated in the fourth Ig domain, is not observed in neurons early in development. In contrast, up to 50% of N-CAM transcripts in neurons of the central nervous system in the adult contain this exon (Small and Akeson, 1990). Inclusion of the VASE sequence leads to loss of N-CAM-dependent neurite outgrowth activity while the cell adhesion function of N-CAM is una ected (Sa ell et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the VASE exon, encoding 10 amino acids situated in the fourth Ig domain, is not observed in neurons early in development. In contrast, up to 50% of N-CAM transcripts in neurons of the central nervous system in the adult contain this exon (Small and Akeson, 1990). Inclusion of the VASE sequence leads to loss of N-CAM-dependent neurite outgrowth activity while the cell adhesion function of N-CAM is una ected (Sa ell et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The VASE-excluding isoform of NCAM-140 (VASE À ) promotes neurite outgrowth, while the VASE-including isoform (VASE + ) inhibits neurite outgrowth (Doherty et al 1992). The embryonic brain mainly expresses VASE À with gradual ascendancy until final dominance of VASE + expression toward adulthood, except in regions such as the olfactory bulb, where reformation of synapses and turnover of neurons continue (Small and Akeson 1990). Thus, the AS of VASE in NCAM-140 is a critical switch for neuronal plasticity.…”
Section: Coupling Of Neuron Projection and Pqbp1 Functionmentioning
confidence: 99%
“…It was recently demonstrated that PSA expression in ciliary ganglion neurons of chick embryo was regulated by PSA synthase level (23). However, it has been shown that the alterations in the extracellular polypeptide structure of NCAM caused by alternative splicing affected the polysialylation of NCAM (31)(32)(33). Therefore, the structural change of NCAM due to a variable alternative spliced exon and the structural changes of N-glycans also regulates the PSA expression level (30,33).…”
Section: St8sia II (Stx) Is An Ncam-specific Psa Synthasementioning
confidence: 99%
“…However, it has been shown that the alterations in the extracellular polypeptide structure of NCAM caused by alternative splicing affected the polysialylation of NCAM (31)(32)(33). Therefore, the structural change of NCAM due to a variable alternative spliced exon and the structural changes of N-glycans also regulates the PSA expression level (30,33). The detailed structural changes of NCAM and its N-glycans during neural development, and in several tissues such as kidney and muscle, are important for understanding regulation of the polysialylation of NCAM.…”
Section: St8sia II (Stx) Is An Ncam-specific Psa Synthasementioning
confidence: 99%